Selenoproteins Protect Against Avian Liver Necrosis by Metabolizing Peroxides and Regulating Receptor Interacting Serine Threonine Kinase 1/Receptor Interacting Serine Threonine Kinase 3/Mixed Lineage Kinase Domain-Like and Mitogen-Activated Protein Kinase Signaling - Li, Tong; Zhang, Jing; Wang, Peng-Jie; Zhang, Zi-Wei; Huang, Jia-Qiang (Frontiers in Physiology, 2021)
Liver necroptosis of chicks is induced by selenium (Se)/Vitamin E (VE) deficiencies and may be associated with oxidative cell damage. To reveal the underlying mechanisms of liver necrosis, a pool of the corn-soy basal diet (10 µg Se/kg; no VE added), a basal diet plus all-rac--tocopheryl acetate (50 mg/kg), Se (sodium selenite at 0.3 mg/kg), or both of these nutrients were provided to day-old broiler chicks (n = 40/group) and for 6 weeks. High incidences of liver necrosis (30%) of chicks were induced by -SE-VE, starting at day 16. The liver Se concentration and glutathione peroxidase (GPX) activity were decreased (P< 0.05) by dietary Se deficiency. Meanwhile, Se deficiency elevated Malondialdehyde (MDA) content and decreased Superoxide dismutasel (SOD) activity in liver at weeks 2 and 4. Chicks fed the two Se-deficient diets showed lower (P< 0.05) hepatic mRNA expression of Gpx1, Gpx3, Gpx4, Selenof, Selenoh, Selenok, Selenom, Selenon, Selenoo, Selenop, Selenot, Selenou, Selenow, and Dio1 than those fed the two Se-supplemented diets. Dietary Se deficiency had elevated (P< 0.05) the expression of SELENOP, but downregulation (P< 0.05) of GPX1, GPX4, SELENON, and SELENOW in the liver of chicks at the two time points. Meanwhile, dietary Se deficiency upregulated (P< 0.05) hepatic protein abundances of p38 mitogen-activated protein kinase (p38), phospho-p38 mitogen-activated protein kinase (p-p38), c-Jun N-terminal kinase (JNK), phospho-c-Jun N-terminal kinase (p-JNK), extracellular signal-regulated kinase (ERK), phospho-mitogen-activated protein kinase (p-ERK), receptor interacting serine threonine kinase 1 (RIPK1), receptor interacting serine threonine kinase 3 (RIPK3), and mixed lineage kinase domain-like (MLKL) at the two time points. In conclusion, our data confirmed the differential regulation of dietary Se deficiency on several key selenoproteins and the RIPK1/RIPK3/MLKL and mitogen-activated protein kinase (MAPK) signaling pathway in chicks and identified new molecular clues for understanding the etiology of nutritional liver necrosis.